The Constitutionality of Health Services as a Public Commodity in the Archipelago - Gustafianof Gustafianof; Muhammad Irham (Bacarita Law Journal, 2026)
The connectivity of health services in the archipelago in Indonesia also requires the development of health service facilities for the community based on the principles of welfare, equity, non-discrimination, participatory, and sustainable. The purpose of this research is related to the constitutional guarantee of equitable distribution of health service facilities in Indonesia that has not been implemented evenly. Especially in areas with archipelago characteristics that require more comprehensive policies, so that health services can reach people in many small islands. The research methods used are normative legal research, and approaches to laws and regulations, legal principles, and legal doctrines. The results of the study found that the design of health services as a public commodity for areas with an archipelago character in accordance with the constitution, forthat it is necessary to synchronize regional regulations in the provision of health service facilities as a form of public commodity in areas with an archipelago character with new laws and regulations is very important to be carried out. In the future, health services as a public commodity must meet the criteria, including: good quality, easy access for the archipelago and there are collective efforts to fulfill health services in islands with an archipelagic character, harmonization of regulations from the central level to the regional level, so that the goal of building health facilities mandated by the constitution can be realized.